PENILAIAN LABORATORIS DAN RADIOLOGIK PADA KASUS NYERI KOLIK RENAL AKIBAT BATU GINJAL DAN BATU URETER DI IGD RSU PUTRI BIDADARI STABAT - INDIRA ALINI; ARIL RIZALDI (LP2MTBM MAKARIOZ, 2022)
Renal colic is a form of low back pain with sudden onset usually originating from the costovertebral angle due to ureteral smooth muscle spasm where the ureteral peristalsis is obstructed by stones, blood clots, and other foreign bodies. Descriptive research method with purposive sampling technique that meets the inclusion and exclusion criteria. Renal colic pain due to kidney stones and ureteral stones is more common in men than women. Based on the most common age above > 50 years, the most common location for colic pain is dextra. Laboratory results of blood leukocytosis as much as 56.4%. Urea values increased and most creatinine values were normal. Urinalysis examination found normal leukocyte cells as much as 56.4% and erythrocyte cells which increased by 56.4%. Nitrite was found negative as much as 96.4%. Cases of renal colic pain with the most diagnosis were ureterolithiasis 52.7%. The most common locations were the renal pyellum 58.3% and the distal ureter 55.6%. The most common size of kidney stones is 1 – 2 cm as much as 37.5% and the size of ureteral stones ranges from < 1 cm as much as 55.6%. The most complications of hydronephrosis were mild grade 52.7%. The number of kidney stones and ureter stones is only one as much as 98.2%. The radiological examination that is often used is ultrasound (87.3%). Based on the results of this study, it can be concluded that the majority of patients with renal colic pain due to kidney stones and ureteral stones are age > 50 years, male gender, location of right renal colic, Most diagnoses were ureteral stones, leukocytosis, negative nitrite, erythrocyturia, stone size, mild hydronephrosis, and ultrasound radiology.